Proceedings of the 16th Annual International Conference on Digital Government Research 2015
DOI: 10.1145/2757401.2757420
|View full text |Cite
|
Sign up to set email alerts
|

Social networks for police and residents in India

Abstract: Safety is a concern for most urban communities; residents interact in multiple ways with the police to address their safety concerns. Positive interactions with police help residents to feel safe. In developing countries, residents have started to use Online Social Networks (OSN) such as Facebook to share concerns and seek solutions. In this study, we investigate whether residents' post on OSN contain actionable information that police can use to address safety concerns and how residents use OSN to communicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, there is a dearth of scholarship conceptualizing the fear of crime in online discourses. A pertinent study conducted by Sachdeva et al (Sachdeva & Kumaraguru, 2015) identified the lexicons in Indian residents' posts and comments on the Facebook page of Bangalore City Police. The results suggested that frequent keywords, such as fear , concern , worried , trouble , notice of , and issue , indicated residents' fear or concerns toward crime and could be applied to monitor public voices and build community policing.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, there is a dearth of scholarship conceptualizing the fear of crime in online discourses. A pertinent study conducted by Sachdeva et al (Sachdeva & Kumaraguru, 2015) identified the lexicons in Indian residents' posts and comments on the Facebook page of Bangalore City Police. The results suggested that frequent keywords, such as fear , concern , worried , trouble , notice of , and issue , indicated residents' fear or concerns toward crime and could be applied to monitor public voices and build community policing.…”
Section: Related Workmentioning
confidence: 99%
“…To the best of our knowledge, there is a dearth of scholarship conceptualizing the fear of crime in online discourses. A pertinent study conducted by Sachdeva et al (Sachdeva & Kumaraguru, 2015) identified the lexicons in Indian keywords, such as fear, concern, worried, trouble, notice of, and issue crime and could be applied to monitor public voices and build community policing. However, the proposed prior work that defined and measured the fear of crime offline and online but focuses on the online discourses about crime.…”
Section: The Fear Of Crime Disclosure In Online Conversationsmentioning
confidence: 99%
See 1 more Smart Citation